1996
DOI: 10.12968/bjon.1996.5.5.303
|View full text |Cite
|
Sign up to set email alerts
|

Study of moving and handling practices on two medical wards

Abstract: This small exploratory pilot study was undertaken to explore the moving and handling practices of nurses working on two medical wards and to determine nurses' perceptions of factors that might influence those practices. Data were collected by means of non-participant observation and semi-structured interviews. The results suggest that risk assessment of the task, load, environment and individual capabilities, carried out in the clinical area, was often incomplete. Factors influencing moving and handling practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…• Patient aversion of the equipment (Bell, 1987;Bewick & Gardner, 2000;Daynard et al, 2001;Evanoff et al, 2003;Garg et al, 1991a;Green, 1996;Laflin & Aja, 1994;McGuire & Dewar, 1995;Meyer, 1995;Moody et al, 1996;Nelson, 2001;Nelson, 2003a;Nelson et al, 2003b;Newman & Callaghan, 1993;Owen & Garg, 1991;Retsas & Pinikahana, 2000;Switzer & Porter, 1993;Takala & Kukkonen, 1987;Yassi et al, 2001). …”
Section: Engineering Controlsmentioning
confidence: 99%
See 1 more Smart Citation
“…• Patient aversion of the equipment (Bell, 1987;Bewick & Gardner, 2000;Daynard et al, 2001;Evanoff et al, 2003;Garg et al, 1991a;Green, 1996;Laflin & Aja, 1994;McGuire & Dewar, 1995;Meyer, 1995;Moody et al, 1996;Nelson, 2001;Nelson, 2003a;Nelson et al, 2003b;Newman & Callaghan, 1993;Owen & Garg, 1991;Retsas & Pinikahana, 2000;Switzer & Porter, 1993;Takala & Kukkonen, 1987;Yassi et al, 2001). …”
Section: Engineering Controlsmentioning
confidence: 99%
“…These devices are placed around the patient's waist and some offer handles which are beneficial to caregivers, as they can perform the transfer more comfortably without suffering a hand or other injury. Moderate evidence indicates that one caregiver should not use a gait belt for vertical transfers of weight bearing patients (Gagnon et al, 1987a;1987b;.While there is agreement that patient handling devices are necessary for safety, (Daynard et al, 2001;Garg et al, 1991a;1991b;Smedley et al 1995), several barriers to use of equipment have been identified, including:• Patient aversion of the equipment (Bell, 1987;Bewick & Gardner, 2000;Daynard et al, 2001;Evanoff et al, 2003;Garg et al, 1991a;Green, 1996;Laflin & Aja, 1994;McGuire & Dewar, 1995;Meyer, 1995;Moody et al, 1996;Nelson, 2001;Nelson, 2003a;Nelson et al, 2003b;Newman & Callaghan, 1993;Owen & Garg, 1991;Retsas & Pinikahana, 2000;Switzer & Porter, 1993;Takala & Kukkonen, 1987;Yassi et al, 2001). …”
mentioning
confidence: 99%
“…Although this was a small study, qualitative data collection by the use of semi‐structured interviews gleaned rich data and Green concluded that nurses had negative attitudes towards changing practice. Training in moving and handling was also deficient as qualified nurses in one ward had received no training in using a hoist (Green, 1996). In a recent Australian survey using a convenient sample of nurses ( N = 523) 40% of respondents reported injuries as a result of patient moving and handling.…”
Section: Moving and Handling Practicementioning
confidence: 99%
“…Research suggests that provision of equipment does not ensure its use, however, as nurses may remain reluctant to use the equipment. The reasons for this are several, including lack of space, lack of training (McGuire & Dewar, 1993; Moody et al ., 1996; Moore & Meakins, 1998), and lack of time, nurses perceiving hoists as being ‘time‐consuming’ (Green, 1996).…”
Section: Lack Of Equipmentmentioning
confidence: 99%